Social knowledge employee: Notion from the theory of intellectual capital [Colaborador social del conocimiento: Noción desde la teoría del capital intelectual] (2017)
The following article aims to conceptualize the social collaborator of knowledge from the notion of intellectual capital. In this sense, several knowledge management models for companies are reviewed and the concept of knowledge worker is defined. Then, the current status of the discussion about the creation and management of knowledge is examined. Finally, the social collaborator of knowledge is conceptualized as a person who, besides comprising the human capital, is integrated into the relational and structural capital through the social relations and the exchange represented by networks.